Stabilisation of grid connected wind farms using doubly-fed induction generators with FACTS controllers. (1st January 2013) - Kumar, N. Senthil
The impact of the wind generation on the power systems is no longer negligible if high penetration levels are going to be achieved. It is very important to boost the transfer capability of the transmission system while improving the utilisation of transmission assets to accommodate high penetration of wind power on the network. Hence, more sophisticated control schemes using advanced power electronic-based flexible AC transmission system (FACTS) controllers are required which will enhance voltage security and voltage stability control. This paper presents the impact of FACTS controllers on the dynamic stability of power systems connected with wind energy conversion systems. The wind farm model considered is a variable speed doubly-fed induction generator model. The dynamic simulation results yield information on 1 the impact of faults and wind speed changes on the performance of DFIG-based induction generators 2 the change in controllable parameters of the FACTS controllers following the faults and wind speed changes 3 transient rating of the FACTS controllers for enhancement of rotor speed stability of induction generators and angle stability of synchronous generators.